A nonlinear fractional-order H∞ observer for SOC estimation of battery pack of electric vehicles. (August 2021) - Yue, Wei; Liu, Cong-zhi; Li, Liang; Chen, Xiang; Muhammad, Fahad
This work is focused on designing a fractional-orderH ∞ observer and applying it into the state of charge (SOC) estimation for lithium-ion battery pack system. Firstly, a fractional order equivalent circuit model based on the fractional capacitor is established and identified. Secondly, the SOC estimation method based on the fractional-orderH ∞ observer is proposed. The nonlinear intrinsic relationship between the open-circuit voltage and SOC is described as a polynomial function, and its Lipschitz proposition has been discussed. Then, the nonlinear observer design criterion is established based on the Lyapunov method. Finally, the effectiveness of the proposed method is verified with high accuracy and robustness by the experiment results.